Invertebrates Ecophysiology and Management - Ray, Sajal; Diarte-Plata, Genaro; Escamilla-Montes, Ruth (IntechOpen, 2020)
Invertebrates exhibit a wide range of diversity in body plan, physiology, behaviour, adaptation and preferences for habitat and food. Their relationship with the environment is unique and multidimensional. This book is organized into two sections containing chapters on the frontier areas of research in ecophysiology and management-related problems of various invertebrates. Topics covered include hibernation physiology; the amelioration potential of drug and parasitic host response of molluscs; the genetics and biology of hydrocorals; and current trends of management, aquaculture, and harvesting of ecologically and economically important molluscs and sponges. This book is an enriched edition of invertebrate zoology and is a useful source of information for researchers and students in various disciplines. In recent years, a paradigm shift in research on invertebrates has occurred under the backdrop of climate change and environmental contamination. This important shift in the research is well reflected in this book.